EVALUATING INDUSTRIAL WORK PRACTICE IN TVET: A MULTI-SITE KIRKPATRICK EVALUATION OF MOTORCYCLE ENGINEERING PROGRAMS IN INDONESIAN VOCATIONAL SCHOOLS - Yuda Prasetia; Widiyanti Widiyanti; Yoto Yoto; Arvieka Sabilla Putri Setiadi (SOSIOEDUKASI, 2026)
Industrial Work Practice (PKL) is a core component of vocational education aimed at improving learners’ work readiness through learning experiences in the industrial world. However, previous studies have typically assessed Industrial Work Practice in isolation, focusing on participant satisfaction, competency gains, or graduate employment without offering a comprehensive evaluation across all levels of Kirkpatrick’s framework. This study aims to evaluate the effectiveness of Industrial Work Practice in the Motorcycle Engineering Skill Program at Vocational Schools using the Kirkpatrick Four-Level Evaluation Model. The study used a qualitative approach with a multi-case study design at two Vocational Schools in Indonesia. Data were collected through in-depth interviews, structured observation, and document analysis involving alumni, supervising teachers, industry supervisors, workshop heads, and school management. Data analysis was conducted using the Miles and Huberman interactive model, while data validity was ensured through triangulation, member checking, and peer debriefing. The findings reveal that Industrial Work Practice is effective at all four levels of Kirkpatrick evaluation. The program provides authentic learning experiences that improve technical and professional competence, encourage behavioral change in the form of increased discipline, responsibility, and communication skills, and strengthen school-industry partnerships and graduate work readiness. Nevertheless, the evaluation system and feedback mechanism for Industrial Work Practice are still not optimally structured. This study’s novelty lies in the comprehensive application of the Kirkpatrick Evaluation Model through a qualitative multi-case approach, producing empirical evidence that supports the development of the Industrial Work Practice evaluation system and the strengthening of school-industry partnerships in vocational education.